A study on the effect of marketing mix elements towards performance of Celcom Axiata Berhad: a case study in Kota Bharu / Rabi’atul’adawiyah Mukhtar - Mukhtar, Rabi’atul’adawiyah (2015)
Nowadays, telecommunication companies are well established and each of them competing each other to be leading on the market. Celcom is among the first telecommunication company in Malaysia. Celcom has their competitive advantage to attract the more customer. This study about the effect marketing mix towards performance of Celcom in Kota Bharu. Marketing mix includes product, price, promotion and place which is given effect or not toward performance. This study was held because, Celcom was not consistent with their revenue and also profit. This study whether the marketing mix give effect or not toward performance business. Through the data collection, this study able to find the effect that gives influence toward the performance of Celcom. There were 150 set of questionnaire has been distributed to respondents. This study also tested the data by reliability analysis, frequency distribution, regression, correlation and also cross tabulation. From the result, shown that product,price and place was significant with performance and promotion was not a significant relationship with the performance of business. Celcom Axiata Berhad can be maintain their the product, the price and the place element, however, Celcom need to improve their promotion to make sure existing and potential customer are attract with their promotion